THE IMPLICATIONS OF LONG DISTANCE MARRIAGE ON HOUSEHOLD HARMONY FROM THE PERSPECTIVE OF ISLAMIC FAMILY LAW: A CASE STUDY IN KRADENAN DISTRICT, GROBOGAN REGENCY - Abdul Halim; Yusdi Haq (Program Pascasarjana UIN Sumatera Utara, 2026)
Increased work mobility among contemporary Muslim families has led to the emergence of long-distance marriage as a form of household adaptation to unavoidable economic pressures. This study aims to analyze the driving factors of long-distance marriage (LDM), its impact on communication, trust, and marital satisfaction, as well as its implications from the perspective of Islamic Family Law through the concept of mu'asyarah bil ma'ruf. The study employs a qualitative approach using a case study design, conducted in Kradenan Subdistrict, Grobogan Regency, involving five informants selected through purposive sampling based on the criterion of currently being in or having previously been in a long-distance marriage for at least one year. Data were collected through in-depth interviews and analyzed through the stages of data reduction, data presentation, and drawing conclusions. The findings indicate that LDM among all informants was primarily driven by economic factors and work demands, rather than as an ideal relational choice. The impact is ambivalent: physical distance increases the risk of loneliness and reduced marital satisfaction, yet simultaneously encourages couples to build more mindful communication and actively maintain trust. An analysis based on the concept of mu'asyarah bil ma'ruf indicates that the indicator of financial support is consistently met, the indicator of respectful communication is met to varying degrees, while the indicator of protection from domestic burdens is the most vulnerable area. This study confirms that mu'asyarah bil ma'ruf is a dynamic and contextual principle, determined not merely by physical presence, but by the quality of the husband’s attention, responsibility, and emotional presence even when separated by distance.